Unexpected Death of a Child with Complex Febrile Seizures—Pathophysiology Similar to Sudden Unexpected Death in Epilepsy? - Dlouhy, Brian J.; Ciliberto, Michael A.; Cifra, Christina L.; Kirby, Patricia A.; Shrock, Devin L.; Nashelsky, Marcus; Richerson, George B. (Frontiers in Neurology, 2017)
Febrile seizures are usually considered relatively benign. Although some cases of sudden unexplained death in childhood (SUDC) have a history of febrile seizures, no documented case of febrile seizure-induced death has been reported. Here we describe a child with complex febrile seizures who died suddenly and unexpectedly after a suspected seizure while in bed at night during the beginning phases of sleep. She was resuscitated and pronounced brain dead two days later at our regional medical center. Autopsy revealed multiorgan effects of hypoperfusion and did not reveal an underlying (precipitating) disease, injury or toxicological cause of death. Although a seizure was not witnessed, it was suspected as the underlying cause of death based on the medical examiner and forensic pathologist (author MN) investigation, the post-resuscitation clinical findings and multiple aspects of the clinical history. The child had a history of complex febrile seizures that had previously caused apnea and oxygen desaturation. She had two febrile seizures earlier on the same day of the fatal event. Interestingly, her mother also experienced a febrile seizure as a child, which led to respiratory arrest requiring cardiorespiratory resuscitation. This case suggests that in a child with complex febrile seizures, a seizure can induce death in a manner that is consistent with the majority of cases of sudden unexpected death in epilepsy (SUDEP). Further work is needed to better understand how and why certain individuals, with a history of epilepsy or not, die suddenly and unexpectedly from seizures. This will only occur through better understanding of the pathophysiologic mechanisms underlying epileptic and febrile seizures and death from seizures including SUDEP.